Black Pride and Black Prejudice - Sniderman, Paul M. (Book collections on Project MUSE., 2002)
Argues that black pride is not inconsistent with American pride, presenting the thoughts of African Americans on how they feel about each other and their country to reveal how African Americans as a group reject racial separatism and do not encourage prejudice toward non-black groups.